Identifikasi Komponen Senyawa Organik dan Uji Aktivitas Antiinflamasi dari Fraksi Etil Asetat Daun Cabai Rawit (Capsicum frutescens L.) - Pradina, Uci; Sapar, Ajuk; Warsidah, Warsidah; Sayekti, Endah; Aritonang, Anthoni Batahan (Al-Kimia, 2022)
Cayenne pepper was known to treat swelling of tissue cells and is thought to have anti-inflammatory activity. The aim study is to examine the anti-inflammatory activity of the ethyl acetate fraction of cayenne pepper and identify the components of organic compounds in the ethyl acetate fraction. The stages of this research include preparation, extraction, partitioning, phytochemical tests, anti-inflammatory activity tests using Human Red Blood Cells (HRBC), and identifying the components of organic compounds they contain. Among the three fractions obtained at the extraction stage, the ethyl acetate fraction had the best activity as an anti-inflammatory at a concentration of 1000 mg/L of 57.77%. The fractionation of the ethyl acetate fraction was carried out using Vaccum Liquid Chromatography (VLC), and four combined fractions were obtained. One of the combined fractions, code EA-4-5, with a weight of 0.188 grams, was analyzed using GC-MS and FTIR. The two main compounds obtained from the GC-MS analysis were dodecanoic acid (25.79%) and (-)-Loliolide (12.86%). The results of the FTIR interpretation of the EA-4-5 fraction showed absorption at a wave number of 3234.62 cm-1 (stretching vibration of the -OH functional group), 3088.03 cm-1 and 3028.24 cm-1 (stretching vibration of the functional group =CH), 2931.8 cm-1 and 2858.51 cm-1 (functional group strain vibration –CH), 1712.79 cm-1 (functional group strain vibration –C=O), and 1606.7 cm-1 (strain vibration functional group –C=C).